Regional infrastructure and firm investment. Theory and empirical evidence for Italy - Francesco Aiello; Alfonsina Iona; Leone Leonida (Queen Mary University of London, Department of Economics, 2009)
We model the channels through which public expenditure on infrastructure influences firm value and shapes its investment decisions via both adjustment costs and marginal profitability of capital. We test these hypotheses by using a large panel of Italian firms. Empirical results show that infrastructure interacts with revenues and costs in shaping firm's profitability of capital and influences its adjustment costs. Finally we find that infrastructure expenditure contributes to reduce the economic gap between the North and the South of Italy. These effects vary across regions and sectors.
Keywords: D21; D62; D92; 330; regional infrastructure; firm's value; corporate investment; Infrastrukturinvestition; Regionale Entwicklung; Geschäftswert; Investition; Anpassungskosten; Regionale Disparität; Italien